Analyzing time-dependent relationships: The impact of unexpected and expected inflation on stock and commodity markets - Roșca, Grigore (2024)
This Master’s thesis attempts to analyse and examine the effects of inflation on market returns for different areas. The research analysis is aimed initially at the stock market returns indices within major global economic regions: United States, Euro Zone19 and OECD countries.